SimpleMating: R‐package for prediction and optimization of breeding crosses using genomic selection - Marco Antônio Peixoto; Rodrigo Rampazo Amadeu; Leonardo Lopes Bhering; Luís Felipe V. Ferrão; Patrício R. Munoz; Márcio F. R. Resende Jr. (The Plant Genome)
Abstract Selecting parents and crosses is a critical step for a successful breeding program. The ability to design crosses with high means that will maintain genetic variation in the population is the goal for long‐term applications. Herein, we describe a new computational package for mate allocation in a breeding program. SimpleMating is a flexible and open‐source R package originally designed to predict and optimize breeding crosses in crops with different reproductive systems and breeding designs. Divided into modules, SimpleMating first estimates the cross performance (criterion), such as mid‐parental value, cross total genetic value, and/or usefulness of a set of crosses. The second module implements an optimization algorithm to maximize a target criterion while minimizing next‐generation inbreeding. The software is flexible, enabling users to specify the desired number of crosses, set maximum and minimum crosses per parent, and define the maximum allowable parent relationship for creating crosses. As an outcome, SimpleMating generates a mating plan from the target parental population using single or multi‐trait criteria. For example, we implemented and tested SimpleMating in a simulated maize breeding program obtained through stochastic simulations. The crosses designed via SimpleMating showed a large genetic mean over time (up to 22% more genetic gain than conventional genomic selection programs, with lesser loss of genetic diversity over time), supporting the use of this tool, as well as the use of data‐driven decisions in breeding programs.